1996
DOI: 10.1084/jem.184.6.2405
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Interleukin (IL)-15 in Regulating the Differentiation of Granulated Metrial Gland Cells in Mouse Pregnant Uterus

Abstract: Previous studies have suggested that granulated metrial gland (GMG) cells are bone marrow– derived lymphoid cells, which differentiate in situ in the mouse pregnant uterus into natural killer (NK)–like cells. Similar to NK cells, GMG cells express an abundant level of cytolytic mediators such as perforin. The factor(s) regulating the differentiation of GMG cells remain(s) to be identified, although cytokines previously implicated in the stimulation/activation of NK cells (e.g., IL-2, IL-6, IL-7, and IL-12) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 24 publications
3
55
0
2
Order By: Relevance
“…Uterine natural killer cells are the most abundant immune cell type at the maternal−fetal interface (27). IL11 significantly reduced placental IL15, required for uNK cell maturation and differentiation (37), and IL18, secreted by uNKs to mediate normal tissue remodeling (38). In accordance, decidual uNK cell numbers were reduced in IL11-treated pregnant mice at mid-gestation.…”
Section: Discussionsupporting
confidence: 63%
“…Uterine natural killer cells are the most abundant immune cell type at the maternal−fetal interface (27). IL11 significantly reduced placental IL15, required for uNK cell maturation and differentiation (37), and IL18, secreted by uNKs to mediate normal tissue remodeling (38). In accordance, decidual uNK cell numbers were reduced in IL11-treated pregnant mice at mid-gestation.…”
Section: Discussionsupporting
confidence: 63%
“…Whether a4b7 + leukocytes are involved in uNK cell differentiation is unclear, although cells of the monocyte/ macrophage lineage have been reported to play a key role as immunoregulatory cells at the maternal/fetal interface. Published data obtained from in situ hybridization studies suggest that macrophages present in the pregnant mouse uterus may be responsible for the production of IL-15 [22], and it has also been shown that macrophages are the major source of IL-12 and IL-18 in most tissues [23,24]. These cytokines were recently shown to be capable of activating NK cells [25,26], and King and co-workers described IL-15 receptor expression on human decidual NK cells [27].…”
Section: Discussionmentioning
confidence: 98%
“…Several cytokines have been implicated in the induction of perforin in cytotoxic cells, including IL-2 (34), IL-6 (35), and IL-15 (36). Of these, IL-15 has been identified as a modulator of perforin expression in mouse uNK cells (37), and it is not inconceivable that NOS-2 acts through IL-15 to regulate perforin expression. NOS-2 has been shown to be a required component of IL-12 signaling in NK cells during early Leishmania major infection (38).…”
Section: Discussionmentioning
confidence: 99%